(untitled) (World of finance, 2022)
Introduction. Construction is one of the key sectors of the Ukrainian economy, the management of which requires deep engineering, logistics and economic knowledge. Among the important resources of the construction industry are technical resources, which are based on construction machinery and equipment. These machines and equipment are systematically used during construction and installation works and significantly facilitate the work of builders and speed up the commissioning of buildings and structures. Unfortunately, not enough attention has been paid to the accounting of construction machinery and equipment as the main technical resources of construction, but it was and is relevant, so we will try to deal with this topic in more detail. The purpose of the article is to classify the main technical resources in construction, analyze the state and form proposals to improve their accounting system and, in particular, the system of analytical accounting accounts. Methods. The study used general methods: systems approach, induction and deduction, synthesis and generalization in order to improve the classification of basic technical resources in construction, as well as special methods in order to analyze the state and form proposals to improve accounting and, in particular, analytical accounting. basic technical resources in construction. Results. The author’s definition of technical resources is formulated and the list of fixed assets that are part of the main technical resources of construction is specified. The dynamics and specific mass of fixed assets in Ukraine, as well as the structure of non-current tangible assets of one of the construction companies are analyzed. The classification of construction machinery and equipment with the indication of potential numbers of their analytical accounts, as well as a number of classification features of such machinery and equipment to meet the information needs of users with management accounting indicators. The information on the largest international manufacturers of construction equipment is generalized. The author’s vision on current issues and some issues of accounting for fixed assets, including the accounting of basic technical resources of construction in terms of reservation and coverage of future current costs for repairs and improvements of health facilities; opening of a separate sub-account 47.4 “Ensuring the restoration of the technical park”; transition to accounting for fixed assets at fair value with documentary evidence of the assessment; separate accounting of operating costs and accounting of maintenance costs of construction machinery and equipment, etc. Perspectives. In further research it is expedient to reveal the tasks, methods and organization of accounting of the main technical resources of construction enterprises using information and computer technologies, first of all, accounting programs of Ukrainian production (“Clerk”, “BAS Accounting”, “IT-Enterprises”, “Master Accounting”, etc.). At the same time, it is necessary to develop research on Ukraine’s economic policy and the formation of financial resources to establish a full cycle of domestic production of construction machinery in Ukrainian machine-building plants in the context of postwar reconstruction of industrial and non-industrial facilities, new approaches to autonomous energy supply of buildings and structures (including energy supply of the houses of the future – “smart homes”), etc.